2019
DOI: 10.1080/20008198.2019.1625700
|View full text |Cite
|
Sign up to set email alerts
|

The association of resilience on psychiatric, substance use, and physical health outcomes in combat trauma-exposed military service members and veterans

Abstract: Objective : Although Combat exposure is associated with a range of psychiatric outcomes, many veterans do not develop psychopathology. Resilience is a multifaceted construct associated with reduced risk of distress and psychopathology; however, few studies have examined the relationship of resilience with a broader spectrum of health outcomes following combat exposure. It also remains important to determine the association of resilience above and beyond other documented risk and protective factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Specifically, while some studies report no differences in the degree of self-reported adversities in females compared to their male counterparts (5,7,17), others find higher levels of self-reported adversities among newly-recruited females soldiers (23)(24)(25). These excessive mental challenges can lead to severe drops in the various domains of QoL in female compared to male soldiers (26,27), as was indeed found in a few recent studies (28,29).…”
Section: Introductionmentioning
confidence: 90%
“…Specifically, while some studies report no differences in the degree of self-reported adversities in females compared to their male counterparts (5,7,17), others find higher levels of self-reported adversities among newly-recruited females soldiers (23)(24)(25). These excessive mental challenges can lead to severe drops in the various domains of QoL in female compared to male soldiers (26,27), as was indeed found in a few recent studies (28,29).…”
Section: Introductionmentioning
confidence: 90%
“…In terms of measurement, panellists highlighted the need to focus efforts on improving assessment in resilience research. For example, factor analytic studies of adapted versions of some resilience measures have not been shown to have good reliability and validity cross-culturally (Jorgensen & Seedat, 2008), and other work suggests that self-rated resilience does not demonstrate concordance with functional ascertainment (Sheerin et al, 2019;Nishimi et al, 2020). This becomes particularly problematic when considering interpreting the results of prior RCTs (see for example Chmitorz et al, 2018).…”
Section: A Research Agendamentioning
confidence: 99%
“…28,29 This could translate into being less stressed and overwhelmed by the functional demands of school. While reports have indicated that post-deployment resiliency is predictive of adaptive psychosocial functioning, 28,30 the authors were unable to find published research that specifically examined differences in resiliency among Veterans as a function of hazardous duty experience. As such, this proposed explanation remains purely speculative.…”
Section: Discussionmentioning
confidence: 99%